Análise da produção de banana orgânica no município de Itapajé - Ceará,Brasil - Andrade, José Alessandro Campos de (2005)
The present research has as main objective to describe the process of organic bananicultura practiced in Itapajé - Ceará, analyzing the aspects social, environmental and economical of this culture’s production. Furthermore, the objective specific are: to analyze organic banana's production after the creation of the Associação dos Fruticultores do Município de Itapajé – AFMI, to make the analyses technique, social and environmental and under the optical of organic banana's consumer's acceptance produced in Itapajé, to analyze the economical viability of the activity for the associated producers AFMI, to discuss some aspects related to the advantages and disadvantages of the production and the organic banana’s market. The study area is located in Itapajé, one of the largest producing of banana of the State of Ceará in Brazil. Itapajé is a city characterized by an intense modification in the physical space in mountainous areas. Primary and secondary datas were used to understand banana's organic production. The present study is classified as analytical-descriptive. Also, an analysis of the economical viability is elaborated for the Association's producers. The analysis of the data was studied through the descriptive statistics instruments and used tables, pictures and illustrations. The organic agriculture in Itapajé is an innovative experience. There are 16 sixteen organic banana´s producers that are linked to AFMI. These producers are developing that activity with many problems, for intance, low infrastructure and precariousness of the roads that harm the production’s drainage. In conclusion, some factors are decisive for the low productivity: the cultural treatments, no irrigation, incipient nutrients’replacement, irregular relief, a stony soil and an old plant banana. It was registered the organic manuring (composting of organic matter). Also, it was registered that the organic banana's producers are concerned with the environmental, they preserve the local biodiversity and they preserve an area of, at least, 20% of forest, the call legal reservation, in organic banana's properties. Finally, this activity of organic banana's production in Itapajé is profitable economically.